(untitled) (Journal of the College of Basic Education, 2022)
Located Rahhaliyah area off the West coast of Razaza which is about the land is relatively flat, and is the drainage basin Razaza area, a geological region characterized by the presence depositions triple time which include the Mkashif Dammam configurations and Euphrates limestone aperture, particularly to the deposition time four-wheel, and that the basis of compositional structure and tectonic Rahhaliyah area are cracks and faults that emit groundwater and major rifts that distinguish them clearly are cracks Abu Gear and Imam Ahmad bin Hashim system. Characterized by an atmosphere hand Rahhaliyah that hot, dry summers and cool limited rains in winter and depending on the climatic data for the station appointed passing year (1992 to 2015), and the application of Thornthwait equation, we find that the total water increase, as was (14.54 mm) for the months December and the second in February, while the total water decrease was (1142.11 mm) for the rest of months a year, and this data is as indicators to show the amount of water available in the study area.